Utilization of Audio Media in Arabic Listening on Arabic Language Education for Students - Kurniawati, Marshelyna; Sunarto, Sunarto; Thoyyibah, Anisatu (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2025)
Istima' is one of the components of passive and active language skills. This study aims to determine the types of audio media and the learning process in Arabic listening or Istima' 2 learning for 2nd semester students of the Arabic Language Education program, Faculty of Islamic Studies, University of Muhammadiyah Malang. This study has a qualitative approach with a case study research type. This research was conducted at the University of Muhammadiyah Malang in the 2018/2019 academic year. The subjects of the study were 2nd semester students of the Arabic Language Education Study Program, class of 2018 who took the Arabic listening or Istima' 2 course, consisting of 2 classes, namely class A and class B. Data collection using observation sheets, interviews, and documentation. The data analysis stage is carried out by collecting the data that has been obtained and then analyzing it with general theories and concepts related to facts to correct or investigate the problem. The results of this study indicate that: (1) The type of media used by lecturers in the istima' learning process uses audio media in the form of Mp3. (2) The Istima' learning process consists of three stages: preparation, learning activities, and closure. The use of audio media in Istima' 2 learning involves playing audio three times, students note down vocabulary that is not yet understood, questions related to vocabulary that is not yet understood, lecturers provide exercises from the material being taught and finally, explanations related to the material contained in the audio.